Вплив світлового режиму та ріверму на індукцію утворення мікробульб картоплі в культурі меристем in vitro - Лавриненко, Ю.О.; Вожегова, Р.А.; Балашова, Г.С.; Котова, О.І. (Фактори експериментальної еволюції організмів, 2014)
Aims. In order to implement new regulators of growth it is necessary to assess their physiological activity according to the integral indicators of growth, plant development and crop yield, and also their interaction with other factors in growing through in vitro culture, such as light intensity and photoperiod. Methods. In order to determine an optimal regime of tuber production in meristem in vitro culture of the potato variety Svitanok Kyivsky under the conditions of a microclonal laboratory an experiment was done according to the generally adopted techniques. There were three factors to study: Factor A – photoperiod (10 and 16 hours), Factor B – light intensity (1500 and 3000 lux), Factor C – the concentration of the growth regulator Riverm (without Riverm; 0.5 and 5.0 mg/l). The observations of the plant growth and development proved that on the 20th day the height gain of the plants and the number of internodes in both photoperiods differed inconsiderably. Results. The productivity of the potato variety Svitanok Kyivsky obtained through in vitro culture depends on the concentration of Riverm, light intensity and photoperiod. Conclusions. In order to provide high intensity of tuber production of the potato variety through in vitro culture it is necessary to use the photoperiod of 16 hours and light intensity of 3000 lux with the concentration of Riverm in nutrient medium of 5.0 mg/l: the weight of an average microtuber being 296.5 mg, the weight of microtubers per plant being 281.5 mg.

Key words: tuber production, plant height, number of internodes, growth regulator, light intensity, nutrient medium, weight of microtubers.